Microbiome characterization of alpine water springs for human consumption reveals site- and usage-specific microbial signatures - Pedron, Renato; Esposito, Alfonso; Cozza, William; Paolazzi, Massimo; Cristofolini, Mario; Segata, Nicola; Jousson, Olivier (Frontiers in Microbiology, 2022)
The microbiome of water springs is gaining increasing interest, especially in water intended for human consumption. However, the knowledge about large-scale patterns in water springs microbiome is still incomplete. The presence of bacteria in water sources used for human consumption is a major concern for health authorities, nonetheless the standard microbiological quality checks are focused only on pathogenic species and total microbial load. Using 16S rRNA high throughput sequencing, we characterised the microbiome from 38 water springs in Trentino (Northern Italy) during two consecutive years in order to gain precious insights on the microbiome composition of these unexplored yet hardly exploited environments. The microbiological studies were integrated with standard measurements of physico-chemical parameters performed by the Provincial Office for Environmental Monitoring in order to highlight some of the dynamics influencing the microbial communities of these waters. We found that alpha diversity showed consistent patterns of variation overtime, and showed a strong positive correlation with the water nitrate concentration and negatively with fixed residue, electrical conductivity and calcium concentration. Surprisingly, alpha diversity did not show any significant correlation with neither pH nor temperature. We found that despite their remarkable stability, different water springs display different coefficients of variation in alpha diversity, and that springs used for similar purposes showed similar microbiomes. Furthermore, the springs could be grouped according to the number of shared species into three major groups: low, mid and high number of shared taxa, and those three groups of springs were consistent with the spring usage. Species belonging to the phyla Planctomycetes and Verrucomicrobia were prevalent and at relatively high abundance in springs classified as low number of shared species, whereas the phylum Lentisphaerae and the Candidate Phyla radiation were prevalent at higher abundance in the mineral and potable springs. The present study constitutes an example for standard water spring monitoring integrated with microbial community composition on a regional scale, and provides information which could be useful in the design and application of future water management policies in Trentino.